Research on Permanent Magnet Synchronous Motor Drive System of Electric Vehicle Based on Fuzzy Control. Issue 4 (May 2019) - Xu, Erwei; Wang, Shuhong; Liu, Xu; Huang, Jiwen
Abstract: The performance of permanent magnet synchronous motor is an important indicator to measure the performance of motor. Since the conventional PID control is only applicable to the linear control system, the conventional PID control cannot satisfy the control performance requirements for a nonlinear control system such as a permanent magnet synchronous motor or a time-varying system. Fuzzy control does not depend on the precise mathematical model of the controlled object, and it has strong robustness and anti-interference ability to the changes of the controlled object parameters. In this paper, the traditional PID control and fuzzy control are combined, and the PID parameters are adjusted online by the fuzzy controller, so that the permanent magnet synchronous motor speed regulation system has good dynamic and static characteristics. In this paper, MATLAB is used to model and simulate the permanent magnet synchronous motor vector control system based on fuzzy control. The results show that the fuzzy controller has excellent performance in suppressing the overshoot and anti-disturbance.